UPAYA MENANGGULANGI BULLYING - Faishal (Ta’dibi : Jurnal Manajemen Pendidikan Islam, 2023)
Bullying remains a topic of discussion and study that is never completed, because the activity always occurs and repeats even with its various variants, along with the development of social life and technological sophistication. So that this bullying case must be a serious concern by all elements of society so that it can be minimized, because the effects of this bullying behavior are very bad, not only for victims of bullying but perpetrators also feel the impact or effects of what they have done. So that through library research or also called this literature study, the author collects library data, reads, records and processes from various sources. The main data sources are from books and journals that discuss bullying behavior both in educational institutions, and in the general public, and are supported by the author's personal experience in the field in managing educational institutions to provide an objective picture of how all components of the nation contribute to overcoming bullying behavior, so that the behavior is decreasing or even no longer exists.